(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article examines the use of complex words in translation from French. Its relevance is due to the constant increase in the number of new words from various languages in the modern French language, which is caused by the continuous development of modern technologies in the world. At the same time, the cultural policy of the French Republic is aimed at protecting its own language. The authors of the article pay special attention to the types and methods of correct and correct translation, taking into account complex words.